Oily drilling cutting modified dry powder, preparation method thereof and well cementation cement slurry

By modifying oil-containing drill cuttings into modified dry powder and compounding them with other components to prepare cementing cement slurry, the high cost and difficulty in supervision in the treatment and resource utilization of oil-containing drill cuttings are solved, and efficient and economical resource-based utilization and green development are achieved.

CN119707338APending Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311259552.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the existing technology treats and resources the use of oil-containing drill chips, there are problems such as large total amount of waste, high harmless disposal cost, low resource utilization, and difficult supervision of the entire process, making it difficult to achieve green development and clean production.

Method used

By using oil-containing drill cuttings as the core, the potassium calcium-magnesium cementitious shell is formed by reacting calcium oxide, potassium dihydrogen phosphate and magnesium oxide, oil-containing drill cutting modified dry powder is prepared, and cement cement slurry is prepared with oil well cement, microsilicon, water-reducing agent and other components.

Benefits of technology

It realizes on-site in-situ modification and resource utilization of oil-containing drill chips, reduces processing costs and energy consumption, improves the strength and density of cementing cement slurry, and meets the requirements of green environmental protection and clean production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707338A_ABST
    Figure CN119707338A_ABST
Patent Text Reader

Abstract

The invention provides oil-containing drilling cutting modified dry powder, a preparation method thereof and well cementation cement slurry. The oil-containing drilling cutting modified dry powder has a shell-core structure, the core is oil-containing drilling cutting, and the shell is potassium calcium magnesium phosphate cement. According to the method provided by the invention, on-site in-situ modification is performed on the oil-containing drilling cuttings, the well cementation cement slurry is directly prepared on site after modification and then is reinjected into a well, additional heating treatment is not needed in the whole process, treatment equipment is simple, the process is simple, the defects of transportation, energy consumption and cost of an oil-containing drilling cutting treatment technology in the prior art are overcome, and reduction and resource utilization of the oil-containing drilling cuttings are realized. The well cementation cement slurry containing the oil-containing drilling cutting modified dry powder has the advantages of no bleeding, no sedimentation, adjustable thickening time, micro-expansion of set cement, high strength, low permeability, low porosity and the like, and is suitable for the formation temperature of 50-110 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization of oil-containing drill cuttings in oil-based drilling fluid and cementing of oil and gas wells, and in particular relates to a modified dry powder of oil-containing drill cuttings, a preparation method thereof and cementing cement slurry. Background Art

[0002] The global shale oil resources are abundant and widely distributed, and the technically recoverable shale oil resources are 618×10 8 Tons, of which China ranks in the top three, accounting for 7% of the total global resources. Based on the needs of national oil strategic security and economic and social development, my country has increased its efforts in shale oil and gas exploration and development. Since the successful commercial development of Fuling shale gas in 2014, shale oil exploration has achieved production capacity breakthroughs in multiple systems of various types of basins, such as the Qingshankou Formation in the Songliao Basin, the second section of the Kongdian Formation in the Cangdong Depression in the Bohai Bay Basin, the fourth section and the third section of the Shahejie Formation in the Jiyang Depression, the seventh section of the Yanchang Formation in the Ordos Basin, the Lucaogou Formation in the Jimusar Depression in the Junggar Basin, the Fengcheng Formation in the Mahu Depression in the Junggar Basin, and the Da'anzhai Section in the Sichuan Basin, showing the huge exploration and development potential of shale oil in China. Relying on the construction of the Jiyang Continental Fault Basin Shale Oil National Development Demonstration Zone, the exploration and development of shale oil in Shengli Oilfield has continued to increase, and it is expected to build a shale oil production capacity of 1 million tons, becoming a realistic successor to Sinopec's large-scale "increase in reserves and build production" of oil and gas resources.

[0003] In order to meet the requirements of safe drilling and well construction of shale oil horizontal wells, diesel-based, white oil-based, and synthetic-based drilling fluid systems with good inhibition, temperature resistance, and lubrication properties are used in the horizontal section of the reservoir. During the drilling process, wastes with a complex composition of drill cuttings, drilling fluid, and formation fluid (such as crude oil) are continuously generated. Taking a 2000m shale oil well in the horizontal well section as an example, a single well can produce more than 600t of oil-containing drill cuttings with an oil content of 12 to 40%. Under natural environmental conditions, it is difficult to degrade, easy to spread, and has high biological toxicity. It can destroy the physical and chemical properties of the soil and pollute water quality through diffusion and migration, and is listed in the national hazardous waste list.

[0004] At present, the oil-bearing drill cuttings in Shengli Oilfield are mainly disposed of harmlessly at the end, such as unified collection and centralized incineration. There are problems such as large total waste volume, high cost of harmless disposal, low degree of resource utilization, and difficulty in supervising the whole process. The environmental protection management problem of oil-bearing drilling cuttings has not been fundamentally solved, which poses a severe challenge to the green development and clean production of shale oil. Therefore, based on the technical needs of oil-bearing drill cuttings reduction and resource utilization, exploring new methods and technologies for resource utilization of oil-bearing drill cuttings, improving the reduction and resource utilization level of oil-bearing drill cuttings, and reducing the disposal cost of oil-bearing drill cuttings are crucial to ensure the green development and clean production of Shengli shale oil.

[0005] At present, the resource utilization of oil-based drill cuttings is mainly concentrated in cement, roadbed materials and building materials. For example, oil-based drill cuttings are used to prepare road subbase materials in roadbed materials, unfired bricks, sintered bricks, concrete, cement and porous ceramics. However, the unfired bricks prepared with oil-based drill cuttings have low overall strength, limited application scope, and the risk of re-leakage and pollution of pollutants; the use of oil-based drill cuttings to prepare sintered bricks is costly, energy-intensive, and will produce waste gas pollution; when using oil-based drill cuttings to prepare concrete, since organic matter and heavy metals in the oil-based drill cuttings are not completely removed from the product, environmental pollution may occur; the use of oil-based drill cuttings to prepare cement is costly and energy-intensive, and the oil-containing drill cuttings need to be specially transported to the cement production plant, which is prone to leakage and pollution during transportation; the use of oil-based drill cuttings to prepare porous ceramics is costly and energy-intensive, and the application scope of the prepared porous ceramics remains to be clarified.

[0006] In summary, the efficient and harmless treatment and resource utilization of drilling waste oil-containing drill cuttings have become a difficult problem and research hotspot in the field of environmental governance in the oil and gas extraction industry. In the existing resource treatment process, the oil-based drill cuttings after the oil phase treatment are mainly recovered, and the oil-containing drill cuttings need to be transported to cement plants or centralized disposal sites, which not only wastes a lot of manpower and material resources, but also easily causes leakage and pollution of oil-containing drill cuttings during transportation; while the oil-based drill cuttings and oil-based drill cuttings ash used in other oil-containing drill cutting resource treatment technologies are grinding products after high-temperature thermal analysis of oil-based drill cuttings, and their high-temperature thermal analysis not only produces toxic and harmful gases, but also has high energy consumption and very high costs. Therefore, it is key to explore more reasonable, scientific, and localized resource treatment technologies to achieve low-cost, high-efficiency harmless treatment and resource utilization of oil-containing drill cuttings. However, the existing treatment methods for oil-containing drill cuttings have problems such as large total amount of waste, high cost of harmless disposal, low degree of resource utilization, and difficulty in supervising the whole process. At present, there is still no better technical means. To this end, based on the technical needs for reducing and recycling oil-containing drill cuttings, exploring efficient, economical and environmentally friendly methods and technologies for processing and utilizing oil-containing drill cuttings is of great significance to ensuring the green development and clean production of shale oil in my country. Summary of the invention

[0007] The first aspect of the present invention provides a modified dry powder of oil-containing drill cuttings, which is a core-shell structure;

[0008] The core is oil-containing drill cuttings, and the shell is made of potassium phosphate calcium magnesium cement;

[0009] The potassium calcium magnesium phosphate cement is a reaction product of potassium dihydrogen phosphate, calcium oxide and magnesium oxide.

[0010] In the present invention, the oil-containing drill cuttings refer to wastes generated during the drilling process that are mixed with drill cuttings, drilling fluid, formation fluid (such as crude oil), etc., which have a complex composition.

[0011] In the present invention, the binder refers to an inorganic substance with a certain mechanical strength.

[0012] According to a specific embodiment of the present invention, the particle size of the oil-containing drill cuttings modified dry powder is 50 to 200 μm;

[0013] and / or

[0014] The shell has a thickness of 1 to 5 μm.

[0015] The second aspect of the present invention provides a method for preparing the modified dry powder of oil-containing drill cuttings as described in the first aspect of the present invention, which comprises the following steps:

[0016] 1) mixing the oil-containing drill cuttings and calcium oxide, adding water to carry out a first reaction, and obtaining surface-modified oil-containing drill cuttings;

[0017] 2) Mixing the surface-modified oil-containing drill cuttings, potassium dihydrogen phosphate and magnesium oxide, adding water to carry out a second reaction, generating the potassium phosphate calcium magnesium cement on the surface of the surface-modified oil-containing drill cuttings, and cooling to obtain the modified dry powder of the oil-containing drill cuttings.

[0018] According to a specific embodiment of the present invention, the amount of the oil-containing drill cuttings is calculated as 100 parts by mass, the amount of calcium oxide is 4 to 9 parts by mass, the amount of potassium dihydrogen phosphate is 8 to 15 parts by mass, the amount of magnesium oxide is 2.5 to 5 parts by mass, the amount of water in step 1) is 2 to 4.5 parts by mass, and the amount of water in step 2) is 2.5 to 5 parts by mass;

[0019] Preferably, the amount of the oil-containing drill cuttings is calculated as 100 parts by mass, the amount of calcium oxide is 6.2 to 8.5 parts by mass, the amount of potassium dihydrogen phosphate is 12 to 15 parts by mass, the amount of magnesium oxide is 3.8 to 5 parts by mass, the amount of water in step 1) is 3 to 4 parts by mass, and the amount of water in step 2) is 3.7 to 4.6 parts by mass;

[0020] Preferably, the amount of the oil-containing drill cuttings is taken as 100 parts by mass, the amount of calcium oxide is 6.2 parts by mass, the amount of potassium dihydrogen phosphate is 12 parts by mass, the amount of magnesium oxide is 3.8 parts by mass, the amount of water in step 1) is 3 parts by mass, and the amount of water in step 2) is 3.7 parts by mass.

[0021] According to a specific embodiment of the present invention, the first reaction is carried out under stirring for 15 to 30 minutes; and / or

[0022] The second reaction is carried out under stirring for 50 to 80 minutes; and / or

[0023] In step 2), the reaction product obtained by the second reaction is cooled to 40 to 50° C., stirring is stopped, and the product is crushed to obtain the modified dry powder of the oil-containing drill cuttings;

[0024] Preferably, the first reaction is carried out under stirring for 20 to 30 minutes; and / or

[0025] The second reaction is carried out under stirring for 55 to 70 minutes; and / or

[0026] In step 2), the reaction product obtained by the second reaction is cooled to 50° C., stirring is stopped, and the product is crushed to obtain the oil-containing drill cuttings modified dry powder;

[0027] Preferably, the first reaction is carried out under stirring for 20 min; and / or

[0028] The second reaction was carried out under stirring for 70 min.

[0029] Preferably, the temperature of the first reaction and the initial temperature of the second reaction are both room temperature (25° C.).

[0030] According to a specific embodiment of the present invention, the stirring speed during the first reaction is 30 to 50 r / min; and / or

[0031] The stirring speed during the second reaction is 50 to 60 r / min;

[0032] Preferably, the stirring speed during the first reaction is 35 to 50 r / min; and / or

[0033] The stirring speed during the second reaction is 50 to 55 r / min;

[0034] Preferably, the stirring speed during the first reaction is 35 r / min; and / or

[0035] The stirring speed during the second reaction is 50 r / min.

[0036] The third aspect of the present invention provides a cementing slurry, which includes oil well cement, oil-containing drill cuttings modified dry powder, microsilicon, fluid loss additive, drag reducer, defoamer and water;

[0037] The modified dry powder of oil-containing drill cuttings is the modified dry powder of oil-containing drill cuttings described in the first aspect of the present invention or the modified dry powder of oil-containing drill cuttings prepared by the method described in the second aspect of the present invention.

[0038] According to a specific embodiment of the present invention, the mass of the oil well cement is calculated as 100%, the amount of the oil-containing drill cuttings modified dry powder is 30 to 60wt%, the amount of the microsilica is 2.5 to 8wt%, the amount of the fluid loss agent is 1.8 to 3.5wt%, the amount of the drag reducer is 0.3 to 0.8wt%, the amount of the defoamer is 0.2 to 0.3wt%, and the amount of water is 52 to 72wt%;

[0039] Preferably, taking the mass of the oil well cement as 100%, the amount of the oil-containing drill cuttings modified dry powder is 40 to 60wt%, the amount of the microsilica is 3.5 to 7wt%, the amount of the fluid loss agent is 2.6 to 3.1wt%, the amount of the drag reducer is 0.3 to 0.65wt%, the amount of the defoamer is 0.2wt%, and the amount of water is 55 to 65wt%.

[0040] According to a specific embodiment of the present invention, the fluid loss additive is a mixture of a polyvinyl alcohol cross-linked polymer and a waterborne epoxy resin; and / or

[0041] The drag reducer is a sulfonated formaldehyde-acetone polycondensate drag reducer (eg, drag reducer USZ); and / or

[0042] The defoamer is a silicone ether copolymer defoamer or a polyether defoamer (such as defoamer DF-E);

[0043] Preferably, the mass ratio of the polyvinyl alcohol cross-linked polymer to the waterborne epoxy resin is (0.2 to 0.4):(0.6 to 0.8);

[0044] Preferably, the water-based epoxy resin is a modified bisphenol A epoxy resin emulsion;

[0045] Preferably, the modified bisphenol A epoxy resin emulsion is an acrylate-modified bisphenol A epoxy resin emulsion;

[0046] Preferably, the solid content of the modified bisphenol A epoxy resin emulsion is 49 to 51%;

[0047] Preferably, the polyvinyl alcohol cross-linked polymer is a polyvinyl alcohol cross-linked polymer obtained by reacting polyvinyl alcohol with a degree of polymerization of 1700 and a degree of alcoholysis of 88% under the action of a cross-linking agent; and / or

[0048] The cross-linking agent is a mixture of boric acid and nano zinc oxide in a mass ratio of (0.5 to 0.8): (0.2 to 0.5);

[0049] Preferably, the polyvinyl alcohol cross-linked polymer is polyvinyl alcohol cross-linked polymer 1788; and / or

[0050] The particle size of the polyvinyl alcohol cross-linked polymer ranges from 100 to 300 meshes.

[0051] According to a specific embodiment of the present invention, the cementing slurry further includes a retarder;

[0052] Preferably, the mass of the oil well cement is taken as 100%, and the amount of the retarder is 0.3 to 1.5 wt %;

[0053] Preferably, the mass of the oil well cement is taken as 100%, and the amount of the retarder is 0.5 to 1.3 wt %;

[0054] Preferably, the retarder is a polymerization product of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and itaconic acid (eg, retarder HX-36L).

[0055] According to a specific embodiment of the present invention, the particle size of the micro silicon is 0.5 to 2 μm.

[0056] Beneficial effects of the present invention:

[0057] In view of the problems in the existing treatment methods of oil-containing drill cuttings, such as a large total amount of waste, high cost of harmless disposal, low degree of resource utilization, and great difficulty in supervising the whole process, the present invention provides a modified dry powder of oil-containing drill cuttings, a preparation method thereof, and cementing cement slurry. The modified dry powder of oil-containing drill cuttings has a shell-core structure, wherein the core is the oil-containing drill cuttings, and the material of the shell is potassium phosphate calcium magnesium cement; the present invention uses the oil-containing drill cuttings as the core, firstly uses calcium oxide to perform surface modification on the oil-containing drill cuttings, and then reacts with potassium dihydrogen phosphate and magnesium oxide, and wraps the potassium phosphate calcium magnesium cement on the surface of the surface-modified oil-containing drill cuttings to form a shell, thereby obtaining the modified dry powder of oil-containing drill cuttings; finally, the modified dry powder of oil-containing drill cuttings is compounded with oil well cement, a fluid loss reducer, a drag reducer, micro-silicon, and a defoaming agent to obtain a cementing cement slurry, and a retarder is preferably added to the cementing cement slurry. Compared with the prior art, the advantages of the modified dry powder of oil-containing drill cuttings, the preparation method thereof, and the cementing cement slurry provided by the present invention are as follows:

[0058] (1) The present invention utilizes calcium oxide to modify the surface of oil-containing drill cuttings, and then further utilizes the reaction of calcium oxide, magnesium oxide, potassium dihydrogen phosphate and water to form potassium calcium magnesium phosphate cement, which is wrapped on the surface of the oil-containing drill cuttings to form a shell, to prepare the modified dry powder of the oil-containing drill cuttings. The method provided by the present invention can modify the oil-containing drill cuttings on site, and after the modification, cementing slurry can be directly prepared on site and injected back into the well. During the whole process, no additional heating device and heating treatment are required, and the processing equipment and processing process are simple, which overcomes the defects of the prior art in terms of transportation, energy consumption and cost of the oil-containing drill cuttings processing technology, realizes the reduction and resource utilization of oil-containing drill cuttings, and effectively ensures the green and environmentally friendly development of oil and gas exploration and development;

[0059] (2) The modified dry powder of oil-containing drill cuttings provided by the present invention has a particle size of 50 to 200 μm, and the shell of potassium calcium magnesium phosphate cementing material coated on its surface is conducive to enhancing the affinity and adhesion of the surface of oil-containing drill cuttings, so that the modified dry powder of oil-containing drill cuttings has good compatibility with various components in cementing cement, such as oil well cement, fluid loss reducer, drag reducer, defoamer and retarder, and can be directly mixed into the on-site cementing ash sample to prepare cementing cement slurry, thereby reducing the adverse effect of oil-containing drill cuttings on the strength of cementing cement; on the other hand, during the preparation process of the modified dry powder of oil-containing drill cuttings, some unreacted calcium oxide and magnesium oxide also help to overcome the system shrinkage characteristics of oil well cement itself, giving the cement stone a micro-expansion property, which helps to improve the bonding quality of the cementing interface, and prepare cementing cement slurry suitable for formation temperatures of 50 to 110°C;

[0060] (3) The cementing slurry containing the modified dry powder of oil-containing drill cuttings provided by the present invention has the advantages of no water separation and no sedimentation, adjustable thickening time, slight expansion of cement stone, high strength, low permeability, low porosity, etc.; in the specific use process, according to the temperature and pressure conditions of the formation, by reasonably optimizing the addition amount of modified dry powder of oil-containing drill cuttings, fluid loss reducer, retarder, drag reducer, etc., a cementing slurry suitable for the formation temperature of 50 to 110°C and meeting the cementing technical standard SY / T 6544-2017 "Performance Requirements of Oil Well Cement Slurry" can be formulated, which has a very broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a scanning electron microscope image of the oil-containing drill cuttings modified dry powder prepared in Example 1;

[0062] Figure 2 EDS analysis of the elemental composition of the potassium calcium magnesium phosphate cement shell material of the oil-containing drill cuttings modified dry powder prepared in Example 1. DETAILED DESCRIPTION

[0063] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation manner does not constitute a limitation of the present invention under any circumstances.

[0064] In the present invention, the raw material information used in each embodiment and each comparative example is as follows:

[0065] Oil-bearing drill cuttings: oil-bearing drill cuttings from on-site drilling in Shengli Oilfield;

[0066] Calcium oxide, magnesium oxide, potassium dihydrogen phosphate: industrial grade products, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0067] Oil well cement: Oil well G grade cement;

[0068] Microsilicon: Provided by Sinopec Shengli Petroleum Engineering Cementing Technology Center, it is a byproduct of the rapid oxidation and condensation of a large amount of highly volatile SiO2 and Si gas produced during the industrial smelting of ferrosilicon and silicon. It is gray-black in color and has a particle size ranging from 0.5 to 2.0 μm.

[0069] Fluid loss reducer: a mixture of polyvinyl alcohol cross-linked polymer and water-based epoxy resin emulsion in a mass ratio of (0.2 to 0.4): (0.6 to 0.8); the polyvinyl alcohol cross-linked polymer is polyvinyl alcohol cross-linked polymer 1788, with a particle size of 100 to 300 mesh, purchased from Chengdu OMEC Petroleum Technology Co., Ltd., wherein the degree of polymerization of polyvinyl alcohol is 1700 and the degree of alcoholysis is 88%, and the cross-linking agent is a mixture of boric acid and nano zinc oxide in a mass ratio of 0.65:0.35; the water-based epoxy resin emulsion is a modified bisphenol A epoxy resin emulsion (the modification is acrylate modification), purchased from Chengdu OMEC Petroleum Technology Co., Ltd., with an epoxy equivalent of 250 to 280 and a density between 1.07 and 1.12 g / cm 3 , pH 7 to 8, solid content 50 ± 1%;

[0070] Retarder: purchased from Chengdu Omeike Petroleum Technology Co., Ltd., model HX-36L, a copolymer of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and itaconic acid, with a liquid appearance and an effective content of 36%;

[0071] Drag reducer: purchased from Henan Weihui Chemical Co., Ltd., model USZ, dark red powder, a sulfonated formaldehyde-acetone condensation polymer drag reducer;

[0072] Defoamer: purchased from Chengdu OMEC Petroleum Technology Co., Ltd., model DF-E, is a polyether-organosiloxane composite defoamer.

[0073] The room temperature below refers to 25°C.

[0074] Preparation of modified dry powder containing oil-containing drill cuttings

[0075] Example 1

[0076] 1) Weigh 100 parts by mass of oil-containing drill cuttings from on-site drilling, add them into a reactor, stir at a speed of 35 rpm, add 6.2 parts by mass of calcium oxide, spray and add 3.0 parts by mass of water, and stir at room temperature at 35 rpm for 20 minutes;

[0077] 2) Continue to add 12 parts by mass of potassium dihydrogen phosphate and 3.8 parts by mass of magnesium oxide, and stir at 90 rpm for 10 minutes at room temperature to fully mix the reactants; spray and add 3.7 parts by mass of water to react to generate a potassium magnesium calcium phosphate cement having strong bonding properties to the surface of the oil-containing drill cuttings, and use the large amount of heat released by the reaction to promote the continuous reaction, and stir the reaction at 50 rpm for 70 minutes to uniformly wrap the potassium magnesium calcium phosphate cement on the surface of the oil-containing drill cuttings; when the product is cooled to 50°C, stop stirring and crush the product to prepare a modified oil-containing drill cuttings dry powder with a potassium calcium magnesium phosphate cement shell thickness of 1 to 5 μm and a particle size of 50 to 200 μm, which is marked as S1.

[0078] Example 2

[0079] 1) Weigh 100 parts by mass of oil-containing drill cuttings from on-site drilling, add them into a reactor, stir at a speed of 50 rpm, add 8.5 parts by mass of calcium oxide, spray and add 4.0 parts by mass of water, and stir at room temperature at 40 rpm for 30 minutes;

[0080] 2) Continue to add 15 parts by mass of potassium dihydrogen phosphate and 5.0 parts by mass of magnesium oxide, and stir at 90 rpm for 14 minutes at room temperature to fully mix the reactants; spray and add 4.6 parts by mass of water to react to generate a potassium magnesium calcium phosphate cement having strong bonding properties to the surface of the oil-containing drill cuttings, and use the large amount of heat released by the reaction to promote the continuous reaction, and stir the reaction at 55 rpm for 55 minutes to uniformly wrap the potassium magnesium calcium phosphate cement on the surface of the oil-containing drill cuttings; when the product is cooled to 50°C, stop stirring and crush the product to prepare a modified oil-containing drill cuttings dry powder with a potassium calcium magnesium phosphate cement shell thickness of 1 to 5 μm and a particle size of 50 to 200 μm, which is marked as S2.

[0081] Test Example 1

[0082] The morphology of the modified dry powder of oil-containing drill cuttings prepared in Examples 1 and 2 was observed by scanning electron microscopy, and the elemental composition of the shell material (i.e., potassium calcium magnesium phosphate cement) on the surface of the modified dry powder of oil-containing drill cuttings prepared in Examples 1 and 2 was analyzed by EDS. Here, the modified dry powder of oil-containing drill cuttings prepared in Example 1 is taken as an example for detailed description.

[0083] Figure 1 This is a scanning electron microscope image of the oil-containing drill cuttings modified dry powder prepared in Example 1. Figure 2 This is an EDS analysis of the elemental composition of the shell material (i.e., potassium phosphate calcium magnesium cement) on the surface of the oil-containing drill cuttings modified dry powder prepared in Example 1. Figure 1 , Figure 2 It is explained that in the modified dry powder of oil-containing drill cuttings prepared in Example 1, the surface of the oil-containing drill cuttings is coated with a shell of potassium calcium magnesium phosphate material (i.e. potassium calcium magnesium phosphate cement) composed of potassium, calcium, phosphorus, oxygen, magnesium, etc.

[0084] It should be noted that the modified dry powder of oil-containing drill cuttings prepared in Example 2 can also be observed under a scanning electron microscope. Figure 1 Similar morphology; the shell of the modified dry powder of oil-containing drill cuttings prepared in Example 2 was confirmed by elemental composition analysis that its components are also potassium phosphate calcium magnesium substances (ie, potassium phosphate calcium magnesium cement) composed of potassium, calcium, phosphorus, oxygen, magnesium, etc.

[0085] Comparative Example 1

[0086] The oil-containing drill cuttings were dried at 120° C. for 12 hours and then crushed to obtain dry powder of the oil-containing drill cuttings with a particle size ranging from 50 to 200 μm.

[0087] Comparative Example 2

[0088] The on-site oil-containing drill cuttings were dried at 500° C. for 12 hours and then crushed to obtain dry oil-containing drill cutting powder with a particle size ranging from 50 to 200 μm.

[0089] Preparation of cementing slurry

[0090] Example 3

[0091] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 40 parts by mass of modified dry powder of oil-containing drill cuttings (S1), 3.5 parts by mass of microsilicon, 2.8 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.2:0.6), 0.37 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 55 parts by mass of water, which is marked as S3.

[0092] Example 4

[0093] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 40 parts by mass of modified dry powder of oil-containing drill cuttings (S1), 3.8 parts by mass of microsilicon, 2.9 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.2:0.7), 0.5 parts by mass of retarder HX-36L, 0.30 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 55 parts by mass of water, which is marked as S4.

[0094] Example 5

[0095] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 40 parts by mass of modified dry powder of oil-containing drill cuttings (S1), 3.8 parts by mass of microsilicon, 3.1 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.2:0.8), 1.2 parts by mass of retarder HX-36L, 0.30 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 55 parts by mass of water, which is marked as S5.

[0096] Example 6

[0097] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 60 parts by mass of modified dry powder of oil-containing drill cuttings (S1), 5.2 parts by mass of microsilicon, 3.0 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.3:0.6), 0.43 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 65 parts by mass of water, marked as S6.

[0098] Example 7

[0099] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 60 parts by mass of modified dry powder of oil-containing drill cuttings (S1), 5.2 parts by mass of microsilicon, 3.0 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.3:0.7), 1.2 parts by mass of retarder HX-36L, 0.36 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 65 parts by mass of water, which is marked as S7.

[0100] Example 8

[0101] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 60 parts by mass of modified dry powder of oil-containing drill cuttings (S1), 7.0 parts by mass of microsilicon, 2.6 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.3:0.8), 1.3 parts by mass of retarder HX-36L, 0.65 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 62 parts by mass of water, which is marked as S8.

[0102] Example 9

[0103] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 40 parts by mass of modified dry powder of oil-containing drill cuttings (S2), 3.5 parts by mass of microsilicon, 2.8 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.4:0.6), 0.37 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 55 parts by mass of water, marked as S9.

[0104] Example 10

[0105] The cementing slurry provided in this embodiment is obtained by mixing the following raw material components in parts by mass: 100 parts by mass of oil well cement, 60 parts by mass of modified dry powder of oil-containing drill cuttings (S2), 7.0 parts by mass of microsilicon, 2.6 parts by mass of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.4:0.7), 1.3 parts by mass of retarder HX-36L, 0.65 parts by mass of drag reducer USZ, 0.2 parts by mass of defoamer DF-E, and 62 parts by mass of water, which is marked as S10.

[0106] Comparative Example 3

[0107] This comparative example is oil well G grade cement slurry with a water-cement mass ratio of 0.44, marked as DS1.

[0108] Comparative Example 4

[0109] The cementing slurry provided in this comparative example is obtained by mixing the following raw material components in parts by weight: 100 parts by weight of oil well cement, 40 parts by weight of the oil-containing drill cuttings dry powder prepared in comparative example 1, 0.2 parts by weight of defoamer DF-E, and 55 parts by weight of water, marked as DS2.

[0110] Comparative Example 5

[0111] The cementing slurry provided in this comparative example is obtained by mixing the following raw material components in parts by weight: 100 parts by weight of oil well cement, 40 parts by weight of the oil-containing drill cuttings dry powder prepared in comparative example 2, 0.2 parts by weight of defoamer DF-E, and 55 parts by weight of water, and is marked as DS3.

[0112] Comparative Example 6

[0113] The cementing slurry provided in this comparative example is obtained by mixing the following raw material components in parts by weight: 100 parts by weight of oil well cement, 40 parts by weight of oil-containing drill cuttings dry powder prepared in comparative example 1, 3.8 parts by weight of microsilicon, 2.9 parts by weight of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to aqueous epoxy resin emulsion is 0.2:0.7), 0.5 parts by weight of retarder HX-36L, 0.30 parts by weight of drag reducer USZ, 0.2 parts by weight of defoamer DF-E, and 55 parts by weight of water, which is marked as DS4.

[0114] Comparative Example 7

[0115] The cementing slurry provided in this comparative example is obtained by mixing the following raw material components in parts by weight: 100 parts by weight of oil well cement, 40 parts by weight of oil-containing drill cuttings dry powder prepared in comparative example 1, 2.4 parts by weight of calcium oxide, 2.7 parts by weight of magnesium oxide, 4.5 parts by weight of potassium dihydrogen phosphate, 3.8 parts by weight of microsilicon, 3.1 parts by weight of fluid loss reducer (wherein the mass ratio of polyvinyl alcohol cross-linked polymer to water-based epoxy resin emulsion is 0.2:0.8), 1.2 parts by weight of retarder HX-36L, 0.30 parts by weight of drag reducer USZ, 0.2 parts by weight of defoamer DF-E, and 55 parts by weight of water, marked as DS5.

[0116] Test Example 2 - Cementing Slurry Performance Determination

[0117] The cementing cement slurries S3 to S10 prepared in Examples 3 to 10 and the cementing cement slurries DS4 and DS5 prepared in Comparative Examples 6 and 7 were used as test objects. The solid dry ash component (i.e., the solid component in the cementing cement slurry raw material) and the liquid water component (i.e., the liquid component in the cementing cement slurry raw material) used to prepare the above cementing cement slurries were weighed and mixed respectively. Then, the slurry was prepared according to the standard GB / T19139-2012 "Test Methods for Oil Well Cement", and the performance of the cementing cement slurry system was tested with reference to the standard SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurries". The test results are shown in Table 1.

[0118] Table 1 Slurry properties of different cementing slurries

[0119]

[0120] As can be seen from Table 1, the cementing slurries containing modified dry powder containing oil-containing drill cuttings prepared in Examples 3 to 10 have good slurry performance at 50 to 110°C, good rheological properties, no water precipitation, controllable water loss and can be controlled at a good level within 50mL, thickening time meets the time requirements of on-site cementing, and the amount of retarder can be adjusted, proving that the slurry performance of the cementing slurry prepared with modified dry powder containing oil-containing drill cuttings provided by the present invention fully meets the requirements of on-site cementing operations. The cementing slurries DS4 and DS5 prepared in Comparative Examples 6 and 7 have poor slurry performance at 50 to 110°C, which is specifically manifested in poor rheological properties, poor sedimentation stability, large water loss, and difficult to adjust thickening time, which cannot meet the requirements of on-site cementing operations. From the formula point of view, compared with Example 4, the cementing cement slurry prepared in Comparative Example 6 replaces the modified dry powder of oil-containing drill cuttings prepared by the present invention with the oil-containing drill cuttings dry powder obtained by simply drying and crushing the same mass of on-site oil-containing drill cuttings at 120°C, indicating that the addition of the oil-containing drill cuttings dry powder to the cementing cement slurry affects the slurry properties of the cementing cement slurry, while the modified dry powder of oil-containing drill cuttings prepared by the present invention has good compatibility with other components of the cementing cement slurry and will not affect the slurry properties of the cementing cement slurry; compared with Example 5, Comparative Example 7 replaces the modified dry powder of oil-containing drill cuttings prepared by the present invention with the oil-containing drill cuttings dry powder obtained by simply drying and crushing the same mass of on-site oil-containing drill cuttings at 500°C, and Moreover, when calcium oxide, magnesium oxide and potassium dihydrogen phosphate are directly added, the slurry performance is the worst, indicating that adding calcium oxide, magnesium oxide and potassium dihydrogen phosphate to cementing cement slurry will not only fail to improve the performance of cementing cement slurry, but will also seriously damage the slurry properties such as rheology and sedimentation stability of cementing cement slurry, resulting in an abnormally short thickening time of cementing cement slurry at 110°C, and the thickening time cannot ensure the construction safety of cementing operation; while the oil-containing drill cuttings modified dry powder coated with potassium calcium magnesium phosphate prepared by the method provided by the present invention will not affect the slurry performance of the cementing cement slurry itself, and the cementing cement slurry further prepared by the oil-containing drill cuttings modified dry powder fully meets the requirements of on-site cementing operations.

[0121] Test Example 3 - Determination of compressive strength and volume expansion rate of cement paste after solidification of cement slurry

[0122] The cementing slurries S3 to S10 prepared in Examples 3 to 10 and the cementing slurries DS1 to DS5 prepared in Comparative Examples 3 to 7 were used as test objects. The solid dry ash component (i.e., the solid component in the cementing slurry raw material) and the liquid water component (i.e., the liquid component in the cementing slurry raw material) for preparing the above cementing slurries were weighed and mixed respectively. Then, the slurry was prepared according to the standard GB / T19139-2012 "Test Method for Oil Well Cement". With reference to the standards SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurry" and SY / T 5504.8-2013 "Evaluation Method for Oil Well Cement Admixtures Part 8: Expansive Agents", the compressive strength and volume expansion rate of the cement paste were measured after curing under different temperature conditions. The test results are shown in Table 2.

[0123] Table 2 Compressive strength and volume expansion rate of cement paste after solidification of different cement slurries

[0124]

[0125] The data in Table 2 show that the cementing cement slurries S3 to S10 prepared in Examples 3 to 10 have strengths of more than 14 MPa after curing for 24 hours at 50 to 110° C. and 20 MPa, and have strengths of more than 26 MPa after curing for 72 hours, both of which have relatively high strengths and meet the requirements for cementing stone strength in cementing standards. In terms of volume expansion rate, it can be seen from Table 2 that after curing for 24 hours at 50 to 110° C. and 20 MPa, the cementing cement slurries prepared in Examples 3 to 10 have no system shrinkage and have slight expansion, which helps to improve the bonding quality of the cementing interface in cementing operations. The cement stone has good performance and fully meets the requirements of on-site cementing operations. The cementing cement slurry DS1 provided in Comparative Example 3 is a G-grade oil well cement slurry. By comparing the data of Examples 3 to 10 with the data of Comparative Example 3, it can be found that at 50°C, 85°C, and 110°C, the cement stone strength of the cementing cement slurry prepared in Examples 3 to 10 after curing for 24 hours is maintained at more than 50% compared with the cement stone strength of the G-grade oil well cement slurry after curing for 24 hours; the volume expansion rate of the G-grade oil well cement slurry after curing for 24 hours under the conditions of 50 to 110°C and 20MPa is about -2%, and the volume shrinks to a small extent, while the cementing cement slurry prepared in Examples 3 to 10 not only does not shrink in volume under the same conditions, but has a slight volume expansion. This shows that the oil-containing drill cuttings modified dry powder prepared by the present invention and other components in the cementing cement slurry not only do not significantly reduce the strength of the oil well cement slurry, but also improve the problem of volume shrinkage of the simple oil well cement slurry. The components of cementing slurries DS2 and DS3 prepared in Comparative Examples 4 and 5 are relatively simple. In addition to the basic oil well cement, defoamer and water components, they only contain dry powder of oil-containing drill cuttings obtained by drying on-site oil-containing drill cuttings at 120°C and 500°C, respectively. Compared with the G-grade cement slurry provided in Comparative Example 3, the addition of oil-containing drill cuttings dry powder significantly reduces the strength of the cement stone formed by the G-grade oil well cement slurry, and after curing for 24 hours at 50 to 110°C and 20MPa, the volume shrinkage is also improved; compared with Example 4, the difference in formula in Comparative Example 6 is that the modified dry powder of oil-containing drill cuttings provided by the present invention used in Example 4 is replaced by an equal mass of oil-containing drill cuttings dry powder. From the results, under the same curing conditions, the strength of the cement stone formed by the cementing cement slurry prepared in Comparative Example 6 is significantly lower than that of the cement stone formed by the cementing cement slurry prepared in Example 4, and the cement stone in Comparative Example 6 shrinks in volume during the curing process. The comparison between Comparative Examples 4, 5 and Comparative Example 3, and the comparison between Comparative Example 6 and Example 4 can illustrate that the addition of the oil-containing drill cuttings dry powder obtained by simply drying the on-site oil-containing drill cuttings to the cementing cement slurry cannot significantly maintain the strength of the cement slurry, nor can it improve or even aggravate the volume shrinkage problem of the cement stone during the curing process.By comparing Comparative Example 7 with Example 5, it can be seen that calcium oxide, magnesium oxide and potassium dihydrogen phosphate are directly added to the cementing cement slurry prepared in Comparative Example 7, while in Example 5, calcium oxide, magnesium oxide and potassium dihydrogen phosphate are used to form potassium calcium magnesium cement as a shell to wrap the surface of oil-containing drill cuttings to obtain oil-containing drill cuttings modified dry powder. Although the volume of the cement stone of the cementing cement slurry prepared in Comparative Example 7 did not shrink during the curing process but also expanded to a certain extent, the strength of the cement stone formed by the cementing cement slurry prepared in Example 7 was significantly lower than the strength of the cement stone formed by the cementing cement slurry prepared in Example 5. It can be proved that directly adding calcium oxide, magnesium oxide and potassium dihydrogen phosphate to the cementing cement slurry cannot improve the strength of the formed cement stone, but will affect the mechanical properties of the cement stone.

[0126] Test Example 4 - Determination of the permeability and porosity of cement paste after cementing slurry

[0127] The cementing cement slurries S3 to S10 prepared in Examples 3 to 10 and the cementing cement slurries DS1 to DS5 prepared in Comparative Examples 3 to 7 were used as test objects. The solid dry ash component (i.e., the solid component in the cementing cement slurry raw material) and the liquid water component (i.e., the liquid component in the cementing cement slurry raw material) for preparing the above cementing cement slurries were weighed and mixed respectively. Then, the slurry was prepared according to the standard GB / T19139-2012 "Test Method for Oil Well Cement". With reference to the standard SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurries", the relative permeability and porosity of the cement stone samples were tested after curing for 72 hours at 85°C and 20MPa. The test results are shown in Table 3.

[0128] Table 3 Permeability and porosity of cement paste after different cement pastes were cured

[0129]

[0130]

[0131] It can be seen from Table 3 that the cement stone formed after the cementing cement slurry prepared in Examples 3 to 10 is cured has lower permeability and porosity than the cement stone formed after the G-grade oil well cement slurry provided in Comparative Example 3 is cured; the cement stone formed after the cementing cement slurry containing oil-containing drill cuttings dry powder prepared in Comparative Examples 4 to 7 is cured has higher permeability and porosity than the cement stone formed after the G-grade oil well cement slurry provided in Comparative Example 3 is cured, which can explain that the modified dry powder of oil-containing drill cuttings obtained by modifying the oil-containing drill cuttings according to the method provided by the present invention can be integrated with additives such as oil well cement, microsilicon, and fluid loss reducer, effectively improve the pore structure inside the cement stone, and form a denser structure, which helps to improve the density of the cement stone, reduce the porosity and permeability, effectively reduce the risk of cross-flow of oil, gas, and water, and is beneficial to cementing and isolating underground oil, gas, and water layers.

[0132] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A modified dry powder of oil-containing drill cuttings, which has a core-shell structure; The core is oil-containing drill cuttings, and the shell is made of potassium phosphate calcium magnesium cement; The potassium calcium magnesium phosphate cement is a reaction product of potassium dihydrogen phosphate, calcium oxide and magnesium oxide.

2. The oil-containing drill cuttings modified dry powder according to claim 1, characterized in that: The particle size of the oil-containing drill cuttings modified dry powder is 50 to 200 μm; and / or The shell has a thickness of 1 to 5 μm.

3. A method for preparing the modified dry powder of oil-containing drill cuttings as claimed in claim 1 or 2, comprising the following steps: 1) mixing the oil-containing drill cuttings and calcium oxide, adding water to carry out a first reaction, and obtaining surface-modified oil-containing drill cuttings; 2) Mixing the surface-modified oil-containing drill cuttings, potassium dihydrogen phosphate and magnesium oxide, adding water to carry out a second reaction, generating the potassium phosphate calcium magnesium cement on the surface of the surface-modified oil-containing drill cuttings, and cooling to obtain the modified dry powder of the oil-containing drill cuttings.

4. The method according to claim 3, characterized in that Taking the amount of the oil-containing drill cuttings as 100 parts by mass, the amount of the calcium oxide is 4 to 9 parts by mass, the amount of the potassium dihydrogen phosphate is 8 to 15 parts by mass, the amount of the magnesium oxide is 2.5 to 5 parts by mass, the amount of water in the step 1) is 2 to 4.5 parts by mass, and the amount of water in the step 2) is 2.5 to 5 parts by mass.

5. The method according to claim 3 or 4, characterized in that: The first reaction is carried out under stirring for 15 to 30 minutes; and / or The second reaction is carried out under stirring for 50 to 80 minutes.

6. A cementing slurry comprising oil well cement, oil-containing drill cuttings modified dry powder, microsilicon, a fluid loss additive, a drag reducer, a defoamer and water; The modified dry powder of oil-containing drill cuttings is the modified dry powder of oil-containing drill cuttings according to claim 1 or 2 or the modified dry powder of oil-containing drill cuttings prepared by the method according to any one of claims 3 to 5.

7. The cementing slurry according to claim 6, characterized in that: Taking the mass of the oil well cement as 100%, the amount of the oil-containing drill cuttings modified dry powder is 30 to 60wt%, the amount of the microsilica is 2.5 to 8wt%, the amount of the fluid loss agent is 1.8 to 3.5wt%, the amount of the drag reducer is 0.3 to 0.8wt%, the amount of the defoamer is 0.2 to 0.3wt%, and the amount of water is 52 to 72wt%.

8. The cementing slurry according to claim 6 or 7, characterized in that: The fluid loss additive is a mixture of a polyvinyl alcohol cross-linked polymer and a waterborne epoxy resin; and / or The drag reducer is a sulfonated formaldehyde-acetone polycondensate drag reducer; and / or The defoamer is a silicone ether copolymer defoamer or a polyether defoamer; Preferably, the mass ratio of the polyvinyl alcohol cross-linked polymer to the waterborne epoxy resin is (0.2 to 0.4):(0.6 to 0.8); Preferably, the water-based epoxy resin is a modified bisphenol A epoxy resin emulsion; Preferably, the modified bisphenol A epoxy resin emulsion is an acrylate-modified bisphenol A epoxy resin emulsion.

9. The cementing slurry according to any one of claims 6 to 8, characterized in that: The cementing slurry also includes a retarder; Preferably, the mass of the oil well cement is taken as 100%, and the amount of the retarder is 0.3 to 1.5 wt %; Preferably, the retarder is a polymerization product of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and itaconic acid.

10. The cementing slurry according to any one of claims 6 to 9, characterized in that: The particle size of the micro silicon is 0.5 to 2 μm.